(Dis)abled young people’s experiences of inclusion in a makerspace: making meaning through collage - Freedman, Esme (Frontiers in Education, 2026)
IntroductionDespite the potential of makerspaces (interdisciplinary, hands-on workshop environments) to provide inclusive non-formal STEM education for (dis)abled young people, little attention has been paid to the experiences of those participating. This research article addresses this gap by exploring the experiences of four (dis)abled young people in a makerspace in the South West of England (three nuerodivergent young people and one neurodivergent young person with a visual impairment).MethodsUsing a multi-method qualitative approach, the study draws on four collages and an audio recording created in a 1.5 hour collage workshop, alongside two elicitation interviews.Results and discussionInductive thematic analysis generated four themes: inclusion as related to social and relational experiences; included through agentic learning/ positioning; included through interdisciplinary opportunities; and inclusion as equal treatment that respects difference. A feminist perspective of disability and inclusion is used to interpret how the participants conceptualized and experienced inclusion/exclusion in the makerspace, attending to both the subjective experience of disability in addition to disabling societal barriers. Findings indicate that the young people experienced the makerspace as an inclusive non- formal learning environment–a place where they could connect with others, be active in their choice of inclusion, and explore interdisciplinary knowledge in creative ways.